Functional Change in Experimental Allodynia After Glutamate-Induced Pain in the Human Masseter Muscle - Shimada, Akiko; Alhilou, Abdelrahman M.; Svensson, Peter; Ernberg, Malin; Christidis, Nikolaos (Frontiers in Oral Health, 2020)
Background: Glutamate, as well as nerve growth factor (NGF), is involved in nociception from peripheral tissues, such as muscles. However, the potential interaction between glutamate and NGF still remains unclear. This study investigated the interaction between glutamate-induced masseter muscle pain and NGF-induced allodynia on pain perception and jaw function in healthy individuals, and any possible sex differences in the response. Materials and methods: Thirty pain-free adult participants (15 men and 15 women, mean age ± SD: 24 ± 4 years) participated in this study consisting of three sessions (Day 0, Day 3 and Day 4). NGF (5 μg/mL, 1.0 mL) was injected into the masseter muscle on Day 0 to induce muscle allodynia. On Day 3, glutamate (1M, 0.2 mL) was injected into the same masseter muscle. Before and after injections on Day 0 and 3, and post-injection (Day 4), spontaneous pain, temporal summation pain, as well as functional pain and fatigue in response to chewing were assessed with validated scales, and the pressure pain threshold (PPT) was recorded. Results: Spontaneous pain intensity was significantly higher after glutamate than NGF (P < 0.001). PPTs, temporal summation pain and functional measures were all reduced 3 days after NGF injection (P’s < 0.001). Injection of glutamate on Day 3 did not further affect PPTs or temporal summation pain and there were no sex differences in the effects (P > 0.189). Chewing pain (P = 0.022) and fatigue increased after glutamate injection to a higher degree in the women than men (P = 0.037). Conclusion: Taken together, while glutamate injected into the NGF-sensitized muscle was painful, it did not alter muscle tenderness in women versus men. However, pain and fatigue evoked by jaw function were higher in women after glutamate injection. This suggest that sex differences reported for masseter myalgia, mimicked by glutamate and NGF mediated pain in this study, may be greater for measures of perceived jaw function, which should be considered in a clinical evaluation.